2015
DOI: 10.1177/0300060515587580
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism rs4263535 in GABRA1 intron 4 was related to deeper sedation by intravenous midazolam

Abstract: Objective: To evaluate whether polymorphisms in the gamma-aminobutyric acid A receptor a1 subunit (GABRA1) gene influence sleep induction time, bispectral index score (BIS) during sleep induction and the total dose of midazolam required to reach a Ramsay Sedation Assessment Scale (RSAS) score of 4. Methods: Patients scheduled for elective orthopaedic surgery were enrolled. All patients received initial doses of 0.02 mg/kg intravenous midazolam. If the RSAS score did not reach 4, an additional 1-mg dose of mida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Finally, a link between sleep-related behaviors and the GABAA receptor genes GABRA1 and GABRA2 (or Gabra1 and Gabra2) has been found in various human and animal studies [18][19][20][21]. However, we did not detect an association of GABRA1 and GABRA2 with sleep duration in the Taiwanese population.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Finally, a link between sleep-related behaviors and the GABAA receptor genes GABRA1 and GABRA2 (or Gabra1 and Gabra2) has been found in various human and animal studies [18][19][20][21]. However, we did not detect an association of GABRA1 and GABRA2 with sleep duration in the Taiwanese population.…”
Section: Discussioncontrasting
confidence: 77%
“…GABAA receptors are coded by GABAA receptor genes such as gamma-aminobutyric acid type A receptor subunit alpha1 (GABRA1). Studies have suggested a connection between GABAA receptor genes and sleeprelated behaviors [18][19][20][21]. For example, Tsai et al [19] indicated a significant association between zolpideminduced complex sleep behaviors and the A15G variant in the GABAA receptor gene GABRA1 in the Taiwanese population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzodiazepines, acting through GABA A receptors, are used for anxiolysis and sedation in the perioperative period. A polymorphism in GABRA1 gene (encoding GABA A receptor) has been shown to influence benzodiazepine sensitivity [110]. Benzodiazepines are metabolized by CYP450 enzymes; midazolam is hydrolyzed by CYP3A4 and CYP3A5 enzymes, while diazepam is a CYP2C19 substrate.…”
Section: Sedative Hypnotics and Volatile Agentsmentioning
confidence: 99%